Bibliometric Analysis of Research Trends and Growth in Farm Media and Agricultural Journalism - Aman Verma; Shahwaz Khan; Ehtesham Ahmad Khan; Sadia Begum; Rupa Rani Sonowal (Indian Journal of Extension Education, 2026)
Farm media encompasses multiple forms of mediation, representational, infrastructural, and elemental that shape the modern agriculture-food system. Although its relevance to sustainable agriculture and rural development is widely acknowledged, a comprehensive synthesis of scholarly contributions to farm media has remained limited. To fill this gap, a bibliometric analysis was carried out on publications from 2005 to 2024, using data from the Web of Science Core Collection and the Dimensions AI database. Data were cleaned and analysed using Biblioshiny and VOSviewer for science mapping. The study examined annual publication trends, citation patterns, journal productivity, keyword co-occurrence, and geographical distributions. Results indicate a sustained rise in publications, reflecting growing interest at the intersection of media, agriculture, and sustainability. The United States leads in output, while Sweden shows high citation impact, and contributions from Nigeria and European countries demonstrate expanding global participation. Keyword mapping identifies dominant and emerging themes in digital agriculture communication and sustainability-focused media practices. In India, where mass media play a crucial role in agricultural extension and rural livelihoods, the limited presence of high-impact studies highlights a significant research and visibility gap. The findings underscore the need for inclusive, collaborative, and context-specific research to strengthen agricultural communication systems globally.